The IMPLEMENTATION OF DIAGNOSTIC ASSESSMENT AS ONE OF THE STEPS TO IMPROVE LEARNING IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Iskak, Kezia Novrina Natasari; A.G Thamrin; Budi Tri Cahyono (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
Diagnostic Assessment is one of the evaluation functions carried out to obtain information on students’ strengths and weaknesses, which is used as a basis for planning Learning according to student circumstances. This study aims to determine the application of diagnostic Assessment in the Independent Curriculum. The method used is a documentary study, where information is obtained from official government documents and articles from the school’s website. Then the information obtained is analyzed descriptively and qualitatively to obtain information that follows the purpose of the study. The results of this study show that this diagnostic Assessment is carried out at the time before planning Learning. The Assessment is conducted using interviews, written tests, and previous learning outcomes. This article will present more in-depth information on the results and discussion.